2018
DOI: 10.1021/acs.biochem.8b00542
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosyl Myoglobins and Their Nitrite Precursors: Crystal Structural and Quantum Mechanics and Molecular Mechanics Theoretical Investigations of Preferred FeNO Ligand Orientations in Myoglobin Distal Pockets

Abstract: The globular dioxygen binding heme protein myoglobin (Mb) is present in several species. Its interactions with the simple nitrogen oxides, namely, nitric oxide (NO) and nitrite, have been known for decades, but the physiological relevance has only recently become more fully appreciated. We previously reported the O-nitrito mode of binding of nitrite to ferric horse heart wild-type (wt) Mb and human hemoglobin. We have expanded on this work and report the interactions of nitrite with wt sperm whale (sw) Mb and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 130 publications
(288 reference statements)
1
11
0
Order By: Relevance
“…Several studies revealed that both haemoglobin (Hb) and myoglobin (Mb) have nitrite reductase activity with the capability to generate NO. [276][277][278] Such heme based nitrite reduction generally proceeds through N-bound nitrite complex as the starting point, similar to that observed for bacterial NiRs. Mechanistic studies revealed that such reduction pathway proceeds to the formation of {FeNO} 7 complexes of Hb or Mb (eqn ( 7) and ( 8)).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Several studies revealed that both haemoglobin (Hb) and myoglobin (Mb) have nitrite reductase activity with the capability to generate NO. [276][277][278] Such heme based nitrite reduction generally proceeds through N-bound nitrite complex as the starting point, similar to that observed for bacterial NiRs. Mechanistic studies revealed that such reduction pathway proceeds to the formation of {FeNO} 7 complexes of Hb or Mb (eqn ( 7) and ( 8)).…”
supporting
confidence: 64%
“…Mechanistic studies revealed that such reduction pathway proceeds to the formation of {FeNO} 7 complexes of Hb or Mb (eqn ( 7) and ( 8)). 277 An alternative possible reduction pathway through O-bound complex was first explored by Radu Silaghi-Dumitrescu in Cd 1 NiR. 279 Theoretical calculations suggested that this reaction proceeded through a protonation from distal histidine residue leading to formation of hydroxo-Fe(III) complex and NO.…”
mentioning
confidence: 99%
“…In addition, the average Ni-Cys bond length ( R Ni–S ) of 2.31 Å in 1 NBP-SP is in excellent agreement with the experimental average value of 2.29 Å and has much better agreement with experiment than the average Ni-Cys bond lengths of 2.35 and 2.44 Å for 1 NBP-TH and 3 NBP-TH, respectively. Additional computational results in Supporting Information (Figure S9) suggest that the protein environment plays a significant role in determining the final electronic and geometric structure for Ni center here, and the full protein QM/MM calculations are needed to reproduce experimental protein results as reported recently …”
Section: Resultsmentioning
confidence: 74%
“…Additional computational results in Supporting Information (Figure S9) suggest that the protein environment plays a significant role in determining the final electronic and geometric structure for Ni center here, and the full protein QM/MM calculations are needed to reproduce experimental protein results as reported recently. 49 Photoinduced H + Reduction by NBP. We next tested whether Ni(II)-NBP can generate H 2 gas under photochemical conditions, employing Ru(bpy) 3 2+ as a photosensitizer and ascorbate as a sacrificial electron donor.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…denitrificans cNOR (PdNOR) with NO that occurred within 2 μs upon photolysis . The reconstructed spectrum was similar to that of the reduced myoglobin NO adduct, with a trough at 430 nm and a peak at 410 nm, overall characteristic of ligand binding to reduced high-spin hemes. Time- and temperature-dependent rapid freeze quench (RFQ) EPR studies identified two Fe–nitrosyl signals within 0.5 ms after NO addition .…”
Section: N2o-forming Enzymesmentioning
confidence: 90%